Research on coordinated control strategy of isolated DC microgrid with PV/hybrid energy storage. (November 2022) - Cui, Junhao; Tian, Guizhen; Liu, Guangchen; Wu, Yuanyuan; Guo, Zihao
Abstract: During the operation of DC microgrid, energy storage system plays an important role in supplying the power difference between distributed generation unit and load and maintaining the voltage stability of DC bus, in recent years, hybrid energy storage technology has gradually attracted the attention of researchers. In this paper, a power distribution control strategy of hybrid energy storage system (HESS) is studied. The droop control based on virtual capacitor is used for the converter of supercapacitor (SC) to realize the power distribution in HESS, and the control strategy is improved to solve the problem that the deviation of bus voltage caused by droop control. Based on the control strategy of HESS, a coordinated control strategy of isolated DC microgrid is studied. By considering SOC of battery and the power demand of load, 3 operation modes of DC microgrid are set. DC microgrid can work in a designated mode under various conditions to achieve efficient and stable operation. Finally, the theory of the above control strategies is verified by the simulation work in RTDS and hardware-in-the-loop experiment based on DSP28335 and RTDS.